2020
DOI: 10.3390/met10020227
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical Stability of a Ti-50.8 at.% Ni Shape Memory Alloy Achieved by Thermal Cycling with a Large Number of Cycles

Abstract: The influence of thermal cycling (TC) with a large number of cycles on the microstructure, the parameters of martensitic transformations (MTs), and the mechanical properties of a Ti-50.8 at.% Ni shape-memory alloy in coarse-grained (CG) and ultrafine-grained (UFG) states was investigated. The effect of microstructural and mechanical stability was found in both coarse-grained and ultrafine-grained states starting from the 100th cycle of martensitic transformations. In addition, an unusual temperature change was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Thirteen research papers have been published in this Special Issue of Metals. The papers cover a wide spectrum of topics, including (i) deformation mechanisms, the mechanical properties and fatigue behaviour of SPD-processed materials [1][2][3][4][5][6][7], (ii) microstructural and mechanical stability at elevated temperatures [8,9], phase formations in alloys [10], the improvement of physical properties (electrical conductivity [11], magneto-resistance [12]) and biomedical properties (biocorrosion resistance [6], biocompatibility [13]) by SPD.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen research papers have been published in this Special Issue of Metals. The papers cover a wide spectrum of topics, including (i) deformation mechanisms, the mechanical properties and fatigue behaviour of SPD-processed materials [1][2][3][4][5][6][7], (ii) microstructural and mechanical stability at elevated temperatures [8,9], phase formations in alloys [10], the improvement of physical properties (electrical conductivity [11], magneto-resistance [12]) and biomedical properties (biocorrosion resistance [6], biocompatibility [13]) by SPD.…”
Section: Contributionsmentioning
confidence: 99%
“…However, a similar decomposition pathway was found. Churakova and Gunderov [9] analysed the influence of thermal cycling on the microstructural and mechanical stability of a Ti-Ni shape memory alloy, which was processed by ECAP, and compared it to a coarse-grained, undeformed counterpart. It was found that the ECAP-processed alloy is more attractive for applications, due to its higher level of properties compared to the coarse-grained state, and its higher stability during thermal cycling.…”
Section: Contributionsmentioning
confidence: 99%
“…The abc pressing [4,5] and equal channel angular pressing (ECAP) [1,[6][7][8] are promising methods for obtaining massive semifinished products from TiNi-based alloys with an ultrafine-grained (UFG) structure. The regularities and features of microstructure evolution in TiNi-based alloys under the action of SPD at 623-773 K are studied in a number of works: [9][10][11][12][13][14][15][16][17][18][19][20][21] after ECAP and [4,5,22,23] after abc pressing. The effect of grain-subgrain structure refinement on the mechanical and inelastic properties of these alloys after ECAP was studied in [9][10][11][12][13][14][15][16][17][18][19][20][21] and after abc pressing in [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The regularities and features of microstructure evolution in TiNi-based alloys under the action of SPD at 623-773 K are studied in a number of works: [9][10][11][12][13][14][15][16][17][18][19][20][21] after ECAP and [4,5,22,23] after abc pressing. The effect of grain-subgrain structure refinement on the mechanical and inelastic properties of these alloys after ECAP was studied in [9][10][11][12][13][14][15][16][17][18][19][20][21] and after abc pressing in [22][23][24][25][26]. It was found that these methods can achieve a refinement of the grain-subgrain structure up to 100-500 nm, depending on the pressing temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation